(3QSGdI dHYV GdMceGA aj GdMLQ GdecQes
(3ChdgG (B:s
(3hCeG GdUfYI GdEdgjI heYQaJgG aEfi CHK Edjc eG jecfi ajgG ef CSQGQ GdMceI GdJi PcQgG GdadGSaI s
(3BNQgG (B:s
(3jJdhf dhf ef GdMeQI MJi jJe dg KdGK SbjGJ hKdGK JThjGJ hKdGK JUYjOGJ eJJGHYGJ ajUjQ CMeQkG bfHGQkG ced gPG GdHGH s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdQGHYs
(3GdQSGdI dHYV GdMceGAs
(3HgG fXGe GdJYbjHIs
(3Jdjg bUjOI dNGdO Hf jRjO aj GdUfYIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdcjejGA h GdWHjYjGJs